2016
DOI: 10.1021/acs.inorgchem.5b02648
|View full text |Cite
|
Sign up to set email alerts
|

High Photothermal Activity within Neutral Nickel Dithiolene Complexes Derived from Imidazolium-Based Ionic Liquids

Abstract: A new series of nickel N,N'-dialkylimidazolidine-2,4,5-trithione complexes ([Ni(R2timdt)2]) carrying linear or branched carbon chains (R = n-C4H9, n-C8H17, n-C12H25, n-C16H33, 2-ethylhexyl, 2-butyloctyl, phytanyl) have been obtained through an original synthetic pathway starting from easily available imidazolium-based ionic liquids. The chemical structures of these nickel complexes were confirmed by NMR and high-resolution mass spectroscopies as well as by X-ray analysis performed on single crystals. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Theexample in Figure 4shows how an LCN strip capable of walking along the laser scanning direction can be reconfigured to undergo ac rawling movement opposite to the laser scanning direction. To achieve light-induced rapid heating and cooling cycles required for light-fueled locomotion process,an ear-infrared (NIR) dye, having strong photothermal response [12] (chemical structure and absorption spectrum in Figure S10), was added into the LCN at 0.2 wt %. Thetemperature in the exposed area could rise to 70 8 8C(above T LC-iso )within 6seconds with alaser (l = 980 nm) intensity of 4.5 Wcm À2 ,a nd cool below T LC-iso upon removal of the laser within few seconds (see Figure S11).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Theexample in Figure 4shows how an LCN strip capable of walking along the laser scanning direction can be reconfigured to undergo ac rawling movement opposite to the laser scanning direction. To achieve light-induced rapid heating and cooling cycles required for light-fueled locomotion process,an ear-infrared (NIR) dye, having strong photothermal response [12] (chemical structure and absorption spectrum in Figure S10), was added into the LCN at 0.2 wt %. Thetemperature in the exposed area could rise to 70 8 8C(above T LC-iso )within 6seconds with alaser (l = 980 nm) intensity of 4.5 Wcm À2 ,a nd cool below T LC-iso upon removal of the laser within few seconds (see Figure S11).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Pioneering research on platinum and nickel charge‐transfer photosensitizers highlights the importance of redox‐active ligands in photoexcited materials. Platinum and nickel dithiolene complexes also show promise as NIR dyes with possible applications in dye sensitized solar cells and photothermal therapy . The ligands in this work are based on the fully oxidized dithione form of the dithiolene ligand that contains a C(=S)‐C(=S) unit, and the dithione unit coordinates to the metal in a charge neutral state .…”
Section: Introductionmentioning
confidence: 99%
“…Platinum and nickel dithiolene complexes also show promise as NIR dyes with possible applications in dye sensitized solar cells [8] and photothermal therapy. [9] The ligands in this work are based on the fully oxidized dithione form of the dithiolene ligand that contains a C(=S)-C(=S) unit, and the dithione unit coordinates to the metal in a charge neutral state. [10] Interconversion between redox states that facilitate charge transfer has been a driving force behind the development of copper ene-1,2-dithiolate(2-) complexes.…”
mentioning
confidence: 99%
“…nickel (II) N,N′-dialkylimidazolidine-2,4,5-trithione complexes ([Ni(R 2 timdt) 2 ]). [29] For this purpose, a new synthetic route starting from commercial and/or easily accessible ionic liquids was developed ( Figure 9a). UV/Vis-NIR absorption studies have confirmed that these complexes strongly absorb in the near infrared around 1000 nm with molar extinction coefficients of the order of 80 000 M -1 cm -1 , among the highest measured for metal-bis(dithiolene) complexes.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…Adapted from ref. [29] mimic the environmental responsiveness of living organisms such as the leaf closure of carnivorous plants, the twisting of plant tendrils, the winding of the tentacles of an octopus ··· [30] Soft robots offer new possibilities to tack problems that cannot be addressed by robots built from rigid bodies. [31] Bio-inspired by these natural features, scientists develop soft actuator materials to transform external stimuli (such as electricity, light, heat, and chemical energy) into mechanical motion.…”
Section: Liquid Crystalsmentioning
confidence: 99%